The Role of Facebook Pro in Marketing Efforts: The Influence of Copywriting, Visual Marketing Promotion, and Community Management on Campaign Success Local Brand in Bandar Lampung - Wulandari Wulandari; Lestari Wuryanti; Ayu Nursari (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the influence of copywriting, visual marketing promotion, and community management on the success of local brand campaigns in Bandar Lampung through the Facebook Pro platform. The research is based on the increasing use of social media as a digital marketing tool by local brands in the fashion and culinary sectors; however, campaign outcomes remain inconsistent. This study employs a quantitative approach using a survey method by distributing questionnaires to business owners and administrators of Facebook Pro accounts of local brands in Bandar Lampung. Multiple linear regression analysis is used to examine both partial and simultaneous effects among variables. The findings indicate that copywriting, visual marketing promotion, and community management have significant partial and simultaneous effects on the success of local brand campaigns. These results confirm that the integration of persuasive messaging, high-quality visual content, and active community engagement plays a crucial role in enhancing engagement, visibility, and overall digital campaign effectiveness. This study provides practical implications for SMEs in optimizing marketing strategies through Facebook Pro and contributes academically to the development of integrated marketing communication studies in social media contexts.